KAJIAN DAMPAK PENAMBANGAN EMAS TANPA IZIN (PETI) TERHADAP LINGKUNGAN SUNGAI BATANG KUANTAN KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI RIAU - Mari Rezki; Zulkarnaini Zulkarnaini; Sofia Anita (Program Pascasarjana Universitas Riau, 2017)
This research was conducted in January 2015 until August 2016 at Batang Kuantan rivers through in Saik Village, Pebaun Hulu Village and Pebaun Hilir Village of Kuantan Mudik subdistrict. The purpose of this study is to analyze the socio-economic circumstances and cultural community as well as the effect of the use of mercury in gold mining without permission (PETI). The study used survey methods, the river water is taken to be brought to the laboratory to be identified physical parameters (temperature, TSS, current velocity) and chemical (DO, BOD5, COD and pH). Data needs, including primary data obtained through questionnaires by respondents and secondary data. The sample size was 45 respondents who work panning for gold and including in Saik Village, Pebaun Hulu Village and Pebaun Hilir Village of Kuantan Mudik subdistrict. With the gold mining Without Permission (PETI) the economic circumstances of local communities to be better than ever because of income or greater income. Social and cultural state of the society changes, people began consumptive, the emergence of prostitution among the food stalls around the gold mine. The use of mercury in the Gold Mining Without Permission (PETI) do not pollute the water environment Batang Kuantan river at the study site because of the mercury content of <0.000024 mg / L is still below the threshold.